Research of the ore reducing furnaces electrical modes for ferronicel production - Shevchenko , D.V.; Ovcharuk , A.M.; Gladkikh , V.A.; Bezugliy , A.V.; Nikolenko , A.V. (Theory and Practice of Metallurgy, 2025)
The paper presents the results of a study of the electrical modes of ferronickel furnaces OTF-1 and OTF-2 at the Pobuzhsky ferronickel plant. It was found that the furnaces operate in arcless mode. An asymmetrical voltage mode is observed: electrode casing - under, which indicates an unbalanced mode of the furnace. As a result of measurements, a significant transfer of power was detected in the area of the electrical circuit of the 4th, 5th, 6th electrodes. An analysis of the electrical mode of a 48 MVA round ferronickel furnace in the city of Hua-Hua (China) showed that the use of a furnace transformer without a voltage booster and an autotransformer makes it possible to provide the necessary electrical mode of ferronickel furnaces. An analysis of the electrical mode of a 90 MVA round ferronickel furnace in Guatemala showed the possibility of operating these furnaces in a combined mode, i.e. in the presence of an electric arc, which is controlled by the resistance of the electrodes and the power ratio in the electric arc and slag.